Development of a microparticle-based dry powder inhalation formulation of ciprofloxacin hydrochloride applying the quality by design approach - Karimi, Keyhaneh (Drug Des Devel Ther, 2016)
Pulmonary drug delivery of ciprofloxacin hydrochloride offers effective local antibacterial activity and convenience of easy application. Spray drying is a trustworthy technique for the production of ciprofloxacin hydrochloride microparticles. Quality by design (QbD), an up-to-date regulatory-based quality management method, was used to predict the final quality of the product. According to the QbD-based theoretical preliminary parameter ranking and priority classification, dry powder inhalation formulation tests were successfully performed in practice. When focusing on the critical parameters, the practical development was more effective and was in correlation with our previous findings. Spray drying produced spherical microparticles. The dry powder formulations prepared were examined by particle size analysis, scanning electron microscopy, Fourier-transform infrared spectroscopy, X-ray powder diffraction, differential scanning calorimetry, and in vitro drug release and aerodynamic particle size analyses were also performed. These formulations showed an appropriate particle size ranging between 2 and 4 μm and displayed an enhanced aerosol performance with fine particle fraction up to 80%.